Molecular Detection and Phylogenetic Analysis of Riemerella anatipestifer in Poultry and Wild Geese in Poland - Anna Sawicka-Durkalec; Grzegorz Tomczyk; Iryna Gerilovych; Olimpia Kursa (Pathogens, 2023)
Riemerella anatipestifer (RA) is one of the most relevant bacterial pathogens of commercial waterfowl from clinical and economic points of view. Our study aimed to evaluate the prevalence of RA infection in different types of commercial poultry in Poland and verify the potential role of wild geese as vectors of this pathogen. We tested a total of 126 poultry flocks, including geese (N = 20), ducks (N = 42), turkeys (N = 64) and 19 wild geese, including greater white-fronted geese (N = 9), greylag geese (N = 5) and Taiga bean geese (N = 5). Tracheal swabs were examined for RA using a PCR targeting a conserved region of the 16S rRNA gene. Selected PCR products were sequenced to perform the phylogenetic analysis. Among the commercial poultry, the highest RA prevalence was found in flocks of ducks (35.7%) and geese (30.0%), whereas the lowest one was found in turkeys (3.2%). Most tested wild geese (94.7%) were RA positive. The phylogenetic analysis showed relatively low genetic diversity of the sequences analyzed, which gathered in two clusters of the phylogenetic tree, and the minimum nucleotide identity was 98.6%. Our results would support the contention that RA isolates from commercial poultry circulate in wild bird populations but are not transmitted back to poultry.